Database systems for adanced applications 16th International Conference, DASFAA 2011, International Workshops: GDB, SIM3, FlashDB, SNSMW, DaMEN, DQIS, Hong Kong, China, April 22-25, 2011. Proceedings - DASFAA (Conference : Database systems) 2011 Hong Kong, China); Xu, Jianliang; Yu, Ge.; Zhou, Shuigeng; Unland, Rainer; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the workshop proceedings of the 16th International Conference on Database Systems for Advanced Applications, DASFAA 2011, held in Hong Kong, China, in April 2011. The volume contains six workshops, each focusing on specific research issues that contribute to the main themes of the DASFAA conference: The First International Workshop on Graph-structured Data Bases (GDB 2011); the First International Workshop on Spatial Information Modeling, Management and Mining (SIM3 2011); the International Workshop on Flash-based Database Systems (FlashDB 2011); the Second International Workshop on Social Networks and Social Media Mining on the Web (SNSMW 2011); the First International Workshop on Data Management for Emerging Network Infrastructures (DaMEN 2011); and the Fourth International Workshop on Data Quality in Integration Systems (DQIS 2011).
Electronic reproduction.
Keywords: Databases -- Congresses; Electronic books